Odrodzenie obywatela w Polsce i NRD szesnaście lat po rozpoczęciu transformacji systemowej - Patkowski, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
In the Author’s opinion, if the development of civic society is to be measured in terms of participation in political life and involvement in non-government organizations East Germans seem to have adapted to the new reality better than Poles. However, if we take into consideration the potential of both nations Poles still stand a chance to build an efficient, and, first of all, their own, modern society. The advantage of having retained their own country, although so often criticized by Poles, may turn out to be fundamental. East Germans could not enjoy this privilege.